2016
DOI: 10.1038/srep39033
|View full text |Cite
|
Sign up to set email alerts
|

Chimera states in uncoupled neurons induced by a multilayer structure

Abstract: Spatial coexistence of coherent and incoherent dynamics in network of coupled oscillators is called a chimera state. We study such chimera states in a network of neurons without any direct interactions but connected through another medium of neurons, forming a multilayer structure. The upper layer is thus made up of uncoupled neurons and the lower layer plays the role of a medium through which the neurons in the upper layer share information among each other. Hindmarsh-Rose neurons with square wave bursting dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(90 citation statements)
references
References 69 publications
0
90
0
Order By: Relevance
“…Some recent reports have also identified chimera states in neuronal systems 5,7,22,23 and superconducting Josephson junctions 24,25 , which encourage a search for future application possibilities. Recent studies have also reported emergence of chimera states in multiplex networks 26 . The effect of initial conditions on chimera states recently investigated using a basin stability approach 27 .…”
Section: Introductionmentioning
confidence: 96%
“…Some recent reports have also identified chimera states in neuronal systems 5,7,22,23 and superconducting Josephson junctions 24,25 , which encourage a search for future application possibilities. Recent studies have also reported emergence of chimera states in multiplex networks 26 . The effect of initial conditions on chimera states recently investigated using a basin stability approach 27 .…”
Section: Introductionmentioning
confidence: 96%
“…Subsequently, links were drawn to unihemispheric sleep, [18][19][20] information processing in biological networks, 21 molecular cell biology dynamics, 22 epileptic seizures, 23,24 social dynamics of cross cultural interactions, 25 dynamics of ecosystems, 26 evolutionary dynamics in biological, social, and ecological systems, 27,28 spin torque nano-oscillators, 29 and quorum sensing mechanisms. 30 Little is known however about the interplay of chimera states across separate networks. Recent studies showed that bidirectional couplings between networks can suppress 31,32 or induce [30][31][32] chimera states in individual networks, and coupling delays were found to play an important role in this multiplexing setting.…”
Section: Introductionmentioning
confidence: 99%
“…30 Little is known however about the interplay of chimera states across separate networks. Recent studies showed that bidirectional couplings between networks can suppress 31,32 or induce [30][31][32] chimera states in individual networks, and coupling delays were found to play an important role in this multiplexing setting. 30,32 Co-existing chimeras were reported to be either identical or non-identical across networks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations